Optimal Dihedral Angle in Twisted Donor–Acceptor Organic Emitters for Maximized Thermally Activated Delayed Fluorescence. (17th November 2022) - Shi, Yuhao; Ma, Huili; Sun, Zhiyu; Zhao, Weijun; Sun, Guangyan; Peng, Qian
Abstract: The twisted donor–acceptor (D‐A) organic formwork with a large dihedral angle ( θ DA ) is usually adopted to narrow the singlet‐triplet energy gap for obtaining excellent thermally activated delayed fluorescence (TADF) emitters. However, the dependence of overall TADF properties on θ DA has not been systematically investigated to this day. Taking new designed CzBP, CzBP‐1M and CzBP‐2M via introducing methyl as investigated models, it is found that (i) with increasing θ DA, the charge transfer component in S1 is larger than that in T1 in varying degrees, leading to non‐monotonic spin‐orbit couplings; (ii) the electron‐vibration couplings between S1 and T1 states become the largest when θ DA approaching 80°, facilitating phonon‐driven up‐conversion; (iii) the overall TADF rate reaches a peak at θ DA ≈80°. By this, the TADF on/off switching is realized via methyl moiety for regulating θ DA from theoretical prediction to experimental confirmation. Importantly, the θ DA near 80° would be a good descriptor for screening excellent D‐A type TADF emitters. Abstract : The physical origin of the optimal dihedral angle of ≈80° in twisted donor–acceptor organic emitters for maximized TADF is deduced and an effective design strategy for efficient TADF emitters is proposed, which provides help for the molecular design and screening of high‐efficiency TADF materials.